Carbon fiber-silk fiber reinforced resin-based composite material as well as preparation method and application thereof
Through the preparation of carbon fiber-silk fiber reinforced resin-based composite materials, combined with thermoplastic toughening modified resin and molding, the problem of insufficient precision and flexibility of flexible antenna surface is solved, and high precision, high flexibility and low cost flexibility are achieved Umbrella antenna surface, suitable for communication equipment in complex environments.
Patent Information
- Application Number
- CN202411710891.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-01-14
AI Technical Summary
The existing wire mesh flexible antenna surface has low accuracy, pure carbon fiber flexible umbrella antenna surface has poor flexibility and low storage ratio, making it difficult to meet complex environments and efficient communication needs.
Using carbon fiber-silk fiber-reinforced resin-based composite material, a flexible umbrella-shaped antenna surface with high precision and high flexibility is prepared through polydopamine modification and carbon oxide nanotube dispersion technology, combined with thermoplastic toughening modified resin and molding.
It improves the accuracy and flexibility of the flexible antenna surface, reduces production costs, enhances the toughness and conductivity of composite materials, and is suitable for communication equipment in variable environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a carbon fiber-silk fiber reinforced resin-based composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of wireless communication technology, antennas, as an important part of wireless communication systems, have a direct impact on the performance of communication systems. The design of traditional antenna surfaces is often limited by materials, shapes and structures, and it is difficult to adapt to complex and changing environmental conditions. However, due to its unique design and characteristics, flexible umbrella-shaped antenna surfaces can be applied to many fields that are difficult for traditional antennas to enter. For example, in the aerospace field, due to space and mass limitations, a flexible antenna that is both lightweight and efficient is required; in the field of military equipment, flexible umbrella-shaped antenna surfaces can adapt to various complex terrains and combat environments; in the field of medical devices, its flexible characteristics can fit the curves of the human body and improve the accuracy and stability of signal reception.
[0003] At present, the existing metal wire mesh flexible antenna surface has the problem of low precision, while the pure carbon fiber flexible umbrella-shaped antenna surface has the problem of poor flexibility and low storage ratio. Therefore, the research on high-precision and high-flexibility flexible umbrella-shaped antenna surface will not only help improve communication performance and expand the scope of application, but also reduce costs and manufacturing difficulties, bringing important impetus to the development of modern communications. Summary of the invention
[0004] In order to solve the above-mentioned problems of low precision and poor flexibility in the existing preparation of flexible umbrella-shaped antenna surfaces, the purpose of the present invention is to provide a carbon fiber-silk fiber reinforced resin-based composite material and a preparation method and application thereof.
[0005] To achieve the above object, the present invention adopts the following technical solution: Firstly, a method for preparing a carbon fiber-silk fiber reinforced resin-based composite material is proposed, comprising the following steps: S1. Prepare a 0.05% to 0.06% by mass aqueous solution of tris(hydroxymethyl)aminomethane, and stir magnetically for 20 min to 30 min to obtain a Tris buffer solution with a pH of 8.2 to 8.8; S2. Add 280% by mass of dopamine hydrochloride to the Tris buffer solution, and continue magnetic stirring for 20 min to 30 min to obtain a DA / Tris-HCl buffer solution; S3. Soak the carbon fiber dry cloth and silk nonwoven fabric in the DA / Tris-HCl buffer solution obtained in S2, soak for 5 to 6 days at room temperature, take out and dry to obtain polydopamine-modified PDA-CF and PDA-NSF, and dry them to room temperature for use; S4. Take another 0.15% to 0.2% mass percentage of oxidized carbon nanotube aqueous solution, add 5 to 7 g of dispersant thereto, and stir ultrasonically for 2 to 2.5 h to obtain a black suspension of OCNTs in which oxidized carbon nanotubes are completely dispersed; S5. Immerse PDA-CF and PDA-NSF into OCNT S The black suspension was kept at room temperature for 5 days to allow the surface and interior of the polydopamine-modified PDA-NSF and PDA-CF to be fully covered with OCNT S The black suspension was then taken out and spread flat in an oven to dry to obtain PDA-CF-OCNT S and PDA-NSF-OCNT S , PDA-CF-OCNT S Denoted as composite material C1 (abbreviated as C1), PDA-NSF-OCNT S It is denoted as composite material S1 (abbreviated as S1).
[0006] Preferably, the dispersant is polyvinyl pyrrolidone.
[0007] Furthermore, the density of the carbon fiber dry cloth is 200g / m 2 ~250g / m 2 , thickness is 0.2mm~0.3mm.
[0008] Furthermore, the density of the silk nonwoven fabric is 50g~80g / m 2 , thickness is 0.1mm~0.15mm.
[0009] The present invention further discloses a carbon fiber-silk fiber reinforced resin-based composite material, which includes composite material C1 and composite material S1 prepared by the above preparation method.
[0010] The present invention further discloses an application of a carbon fiber-silk fiber reinforced resin-based composite material, wherein the carbon fiber-silk fiber reinforced resin-based composite material is prepared according to the above-mentioned preparation method, and the application method is: using the carbon fiber-silk fiber reinforced resin-based composite material to prepare a laminated cloth structure suitable for a flexible antenna surface.
[0011] Furthermore, the preparation method of the laminated fabric structure is: the composite materials C1 and the composite materials S1 are layered in a certain layering order, and then compounded with thermoplastic elastomer polyurethane during a compression molding process to obtain a laminated fabric structure suitable for a flexible umbrella-shaped antenna surface.
[0012] Furthermore, the method for preparing the laminated fabric structure specifically comprises the following steps: A. dissolving a thermoplastic elastic polyurethane having a solid content of 20% in an ethyl acetate solution having a mass percentage of 100% to obtain a mixed solution for standby use; B. Laying the composite material C1 and the composite material S1 in the order of C1-S1-S1-C1; C. During the layering process, the overall curing is carried out using a compression molding technology with a temperature matching that of the thermoplastic toughened modified resin, and the mold is demolded after the temperature is lowered, ultimately obtaining a laminated fabric structure suitable for a flexible umbrella-shaped antenna surface.
[0013] Specifically, in step C, the curing conditions are: 115-125 degrees Celsius, 2-4 MPa pressure, and compression curing for 30-40 minutes.
[0014] Preferably, in step C, the temperature after cooling is 38°C to 42°C Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adopts a molding method of combining thermoplastic toughened modified resin with carbon fiber dry cloth and silk non-woven dry cloth and molding to prepare a laminated cloth structure suitable for flexible antenna surface. The molded high-precision flexible umbrella-shaped antenna surface no longer requires large-scale special equipment such as autoclaves, thereby reducing production costs and improving production efficiency.
[0015] 2. The present invention introduces silk non-woven fabric and carbon fiber dry fabric as a reinforcing structure, thereby improving the flexibility of the carbon fiber dry fabric after being combined with the resin alone, while taking into account the advantages of environmental protection, light weight, durability, etc.
[0016] 3. Through OCNT S The introduction of can not only increase the toughness of the composite material, but also create a stronger interface bonding force between the fiber and the resin, which significantly improves the performance of the final composite material.
[0017] 4. OCNT S The addition of makes the insulating silk non-woven fabric (NSF) conductive, improves the conductivity of carbon fiber, and makes the final laminated cloth structure have ideal conductivity, which is beneficial to the emission and collection of umbrella-shaped antenna surface signals.
[0018] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows.
[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods. DETAILED DESCRIPTION
[0020] The content of the present invention can be further understood by combining the following detailed description of the preferred implementation method of the present invention and the embodiments included. Unless otherwise stated, all technical and scientific terms used in this article have the same meaning as those of ordinary skill in the art to which the present invention belongs. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in the present invention, the definition of the term provided in the present invention shall prevail.
[0021] In a typical embodiment of the present application, a method for preparing a carbon fiber-silk fiber reinforced resin-based composite material is provided, comprising the following steps: S1. Prepare a 0.05% to 0.06% by mass aqueous solution of tris(hydroxymethyl)aminomethane, and stir magnetically for 20 min to 30 min to obtain a Tris buffer solution with a pH of 8.2 to 8.8; S2. Add 280% by mass of dopamine hydrochloride to the Tris buffer solution, and continue magnetic stirring for 20 min to 30 min to obtain a DA / Tris-HCl buffer solution; S3. Soak the carbon fiber dry cloth and silk nonwoven fabric in the DA / Tris-HCl buffer solution obtained in S2, soak for 5 to 6 days at room temperature, take out and dry to obtain polydopamine-modified PDA-CF and PDA-NSF, and dry them to room temperature for use; S4. Take another 0.15% to 0.2% mass percentage of oxidized carbon nanotube aqueous solution, add 5 to 7 g of dispersant thereto, and stir ultrasonically for 2 to 2.5 h to obtain a black suspension of OCNTs in which oxidized carbon nanotubes are completely dispersed; S5. Immerse PDA-CF and PDA-NSF into OCNT S The black suspension was kept at room temperature for 5 days to allow the surface and interior of the polydopamine-modified PDA-NSF and PDA-CF to be fully covered with OCNT S The black suspension was then taken out and spread flat in an oven to dry to obtain PDA-CF-OCNT S and PDA-NSF-OCNT S , PDA-CF-OCNT S Denoted as composite material C1 (abbreviated as C1), PDA-NSF-OCNT S It is denoted as composite material S1 (abbreviated as S1).
[0022] The above preparation method improves the toughness of the carbon fiber dry cloth itself after being combined with the resin by introducing the silk non-woven fabric as a reinforcing structure, while taking into account the advantages of environmental protection, light weight, durability, etc.
[0023] In some specific embodiments, the dispersant may preferably be polyvinyl pyrrolidone.
[0024] In another typical embodiment of the present application, a carbon fiber-silk fiber reinforced resin-based composite material is provided, which includes a composite material C1 and a composite material S1 prepared by modifying a carbon fiber dry cloth and a silk non-woven fabric as a reinforcing structure, both of which are prepared by modifying a polydopamine buffer solution and an oxidized carbon nanotube suspension.
[0025] As a further improvement to the above embodiment of the present invention, the density of the carbon fiber dry cloth is preferably 200 g / m 2 ~250g / m 2 , the thickness is preferably 0.2mm~0.3mm.
[0026] As a further improvement to the above-mentioned embodiment of the present invention, the density of the silk nonwoven fabric is preferably 50g~80g / m 2 , the thickness is preferably 0.1mm~0.15mm.
[0027] In another typical embodiment of the present application, an application of a carbon fiber-silk fiber reinforced resin-based composite material is provided, wherein the carbon fiber-silk fiber reinforced resin-based composite material is used to prepare a laminated cloth structure suitable for a flexible antenna surface.
[0028] Furthermore, the preparation method of the laminated fabric structure is: the composite materials C1 and the composite materials S1 are layered in a certain layering order, and then compounded with thermoplastic elastomer polyurethane during a compression molding process to obtain a laminated fabric structure suitable for a flexible umbrella-shaped antenna surface.
[0029] Furthermore, the method for preparing the laminated fabric structure specifically comprises the following steps: A. dissolving a thermoplastic elastic polyurethane having a solid content of 20% in an ethyl acetate solution having a mass percentage of 100% to obtain a mixed solution for standby use; B. Laying the composite material C1 and the composite material S1 in the order of C1-S1-S1-C1; C. During the layering process, the overall curing is carried out using a compression molding technology with a temperature matching that of the thermoplastic toughened modified resin, and the mold is removed after the temperature is lowered to 38°C~42°C, ultimately obtaining a laminated fabric structure suitable for a flexible umbrella-shaped antenna surface.
[0030] In some specific embodiments, in step C, the curing conditions are: 115-125 degrees Celsius, 2-4 MPa pressure, and compression curing for 30-40 minutes.
[0031] In some specific embodiments, the thermoplastic toughened modified resin is preferably a product of model number toughened TPU SF-64D produced by Kunshan Shoufa Plastic Chemical Co., Ltd.
[0032] The present invention will be further described below in conjunction with embodiments: Example 1 This embodiment firstly relates to a method for preparing a carbon fiber-silk fiber reinforced resin-based composite material, comprising the following steps: S1. First, 0.1% tris(hydroxymethyl)-amino-methane (Tris) was dissolved in 200% deionized water, and stirred with a magnetic stirrer for 20 minutes to obtain a Tris buffer solution with a pH of 8.5; S2. Add 280% dopamine hydrochloride (DA) to the Tris buffer solution and continue magnetic stirring for 20 min to obtain a DA / Tris-HCl buffer solution; S3. The density is 200g / m 2 , T300 twill carbon fiber dry cloth (CF) with a thickness of 0.2mm and a density of 50g / m 2 , a 0.1 mm thick silk nonwoven fabric (NSF) was immersed in the DA / Tris-HCl buffer solution obtained in S2, and then taken out and dried in an electric blast oven at room temperature for 5 days to obtain polydopamine-modified PDA-CF and PDA-NSF, which were then dried to room temperature for later use; S4. Add 5 g of polyvinyl pyrrolidone (PVP) to a 0.15% aqueous solution of oxidized carbon nanotubes (OCNTs), and then stir ultrasonically for 2 h to obtain a black suspension of OCNTs in which OCNTs are completely dispersed and uniformly dispersed; S5. Immerse PDA-CF and PDA-NSF into OCNT S The black suspension was kept at room temperature for 5 days to allow the surface and interior of the polydopamine-modified PDA-NSF and PDA-CF to be fully covered with OCNT S The black suspension was then taken out and spread flat and placed in an electric hot air oven for drying for 6 h to obtain PDA-CF-OCNT S and PDA-NSF-OCNT S Two modified dry fabrics, PDA-CF-OCNT S Denoted as composite material C1 (abbreviated as C1), PDA-NSF-OCNT S It is denoted as composite material S1 (abbreviated as S1).
[0033] Example 2 On the basis of Example 1, this example uses the carbon fiber-silk fiber reinforced resin-based composite material (including C1 and S1) prepared in Example 1 to prepare a laminated fabric structure suitable for a flexible antenna surface. The specific preparation method is as follows: A thermoplastic elastic polyurethane (TPU) having a solid content of 20% was prepared and dissolved in an ethyl acetate solution having a mass percentage of 100% for later use.
[0034] The two modified cloths C1 and S1 were layered in the order of C1-S1-S1-C1. After the layering was completed, an ethyl acetate solution of thermoplastic elastic polyurethane (TPU) with a solid content of 20% was evenly poured on the surface of the C1 cloth, and then the mold was quickly closed. The mold was heated to 120°C, kept warm for 30 minutes, and pressurized at 3Mpa for curing. The mold was cooled to 40°C for demolding, and finally a laminated cloth structure suitable for a flexible umbrella-shaped antenna surface was obtained.
[0035] By combining thermoplastic toughened modified resin with carbon fiber dry cloth and silk non-woven dry cloth and molding, a laminated cloth structure suitable for flexible antenna surface is prepared. The high-precision flexible umbrella-shaped antenna surface no longer requires large-scale special equipment such as autoclaves, which reduces production costs and improves production efficiency. In addition, OCNT S The introduction of OCNT can not only increase the toughness of the composite material, but also create a stronger interface adhesion between the fiber and the resin, which significantly improves the performance of the final composite material. S The addition of makes the insulating silk non-woven fabric (NSF) conductive, improves the conductivity of carbon fiber, and makes the final laminate have an ideal conductivity (30S / m), which is beneficial to the emission and collection of signals of the umbrella-shaped antenna surface.
[0036] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a carbon fiber-silk fiber reinforced resin-based composite material, characterized in that: The following steps are involved: S1. Prepare a 0.05% to 0.06% by mass aqueous solution of tris(hydroxymethyl)aminomethane, and stir magnetically for 20 min to 30 min to obtain a Tris buffer solution with a pH of 8.2 to 8.8; S2. Add 280% by mass of dopamine hydrochloride to the Tris buffer solution, and continue magnetic stirring for 20 min to 30 min to obtain a DA / Tris-HCl buffer solution; S3. Soak the carbon fiber dry cloth and silk nonwoven fabric in the DA / Tris-HCl buffer solution obtained in S2, soak for 5 to 6 days at room temperature, take out and dry to obtain polydopamine-modified PDA-CF and PDA-NSF, and dry them to room temperature for use; S4. Take another 0.15% to 0.2% mass percentage of oxidized carbon nanotube aqueous solution, add 5 to 7 g of dispersant thereto, and stir ultrasonically for 2 to 2.5 h to obtain a black suspension of OCNTs in which oxidized carbon nanotubes are completely dispersed; S5. Immerse PDA-CF and PDA-NSF into OCNT S The black suspension was kept at room temperature for 5 days to allow the surface and interior of the polydopamine-modified PDA-NSF and PDA-CF to be fully covered with OCNT S The black suspension was then taken out and spread flat in an oven to dry to obtain PDA-CF-OCNT S and PDA-NSF-OCNT S , PDA-CF-OCNT S The composite material is named C1. S It is recorded as composite material S1.
2. The method for preparing the carbon fiber-silk fiber reinforced resin-based composite material according to claim 1, characterized in that: The dispersant is polyvinyl pyrrolidone.
3. The method for preparing the carbon fiber-silk fiber reinforced resin-based composite material according to claim 1, characterized in that: In S3, the density of the carbon fiber dry cloth is 200g / m 2 ~250g / m 2 , thickness is 0.2mm~0.3mm.
4. The method for preparing the carbon fiber-silk fiber reinforced resin-based composite material according to claim 1, characterized in that: In S3, the density of the silk nonwoven fabric is 50g~80g / m 2 , thickness is 0.1mm~0.15mm.
5. A carbon fiber-silk fiber reinforced resin-based composite material, characterized in that: The composite material comprises a composite material C1 prepared by the preparation method according to any one of claims 1 to 4 and a composite material S1。 6. An application of a carbon fiber-silk fiber reinforced resin-based composite material, wherein: The carbon fiber-silk fiber reinforced resin-based composite material is prepared according to the preparation method described in any one of claims 1-4, or using the carbon fiber-silk fiber reinforced resin-based composite material described in claim 5, and is characterized in that: the application method is: using the carbon fiber-silk fiber reinforced resin-based composite material to prepare a laminated cloth structure suitable for a flexible antenna surface.
7. The use of the carbon fiber-silk fiber reinforced resin-based composite material as claimed in claim 6, characterized in that: The preparation method of the laminated fabric structure is as follows: composite materials C1 and composite materials S1 are layered in a certain layering order, and then compounded with thermoplastic elastomer polyurethane during a compression molding process to obtain a laminated fabric structure suitable for a flexible umbrella-shaped antenna surface.
8. The use of the carbon fiber-silk fiber reinforced resin-based composite material as claimed in claim 6, characterized in that: The method for preparing the laminated fabric structure specifically comprises the following steps: A. dissolving a thermoplastic elastic polyurethane having a solid content of 20% in an ethyl acetate solution having a mass percentage of 100% to obtain a mixed solution for standby use; B. Laying the composite material C1 and the composite material S1 in the order of C1-S1-S1-C1; C. During the layering process, the overall curing is carried out using a compression molding technology with a temperature matching that of the thermoplastic toughened modified resin, and the mold is demolded after the temperature is lowered, ultimately obtaining a laminated fabric structure suitable for a flexible umbrella-shaped antenna surface.
9. The use of the carbon fiber-silk fiber reinforced resin-based composite material as claimed in claim 8, characterized in that: In step C, the curing conditions are: using a pressure of 2-4 MPa at 115-125 degrees Celsius and molding for 30-40 minutes.
10. The use of the carbon fiber-silk fiber reinforced resin-based composite material as claimed in claim 8, characterized in that: In step C, the temperature after cooling is 38°C to 42°C.